Peran Literasi Ekonomi dan Kegiatan P5 Kewirausahaan terhadap Minat Berwirausaha - Karlina, Elin (Universitas Syiah Kuala, 2025)
This study aims to determine the effect of economic literacy variables and P5 Entrepreneurship activities on entrepreneurial interest in students at SMAN 21 Bekasi City. The population in this study were 280 students of class XI SMAN 21 Bekasi City. The sample consisted of 30 students of class XI taken by random sampling. The data collection technique used a Likert scale questionnaire. Data analysis techniques with Analysis techniques with multiple correlation tests, multiple regression tests, determinant coefficient tests, F tests, and t tests. The results of the study are 1. There is a significant influence together between the economic literacy variables and P5 Entrepreneurship on entrepreneurial interest in SMAN 21 Bekasi City because the significant value is 0.028 0.05. 2. There is no significant influence of the economic literacy variable on entrepreneurial interest in SMAN 21 Bekasi City because the significant value is 0.978 0.05. 3. There is a significant influence of the P5 Entrepreneurship variable on entrepreneurial interest in SMAN 21 Bekasi City because the significant value is 0.014 0.05.